Effectiveness of Insulin Injection Technique on Glycemic Control of Fasting Plasma Glucose and HbA1c in Type II DM Patients at Hasanuddin University Hospital: Randomized Controlled Trial - Semi, Herlina; Ahmad, Sitti Musdalifah; Tuti, Meylani; Islam, Alif Muhammad (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Aims: To identify the effectiveness of insulin injection techniques (injection method, injection location, insulin pen, and drug dose) on glycemic control of HbA1c and Fasting Plasma Glucose (FPG) in Type II DM patients. Methods: The design of this study was quantitative experimental using a Randomized Controlled Trials (RCT) research design with non-blinding in patients with Type II Diabetes Mellitus who had received insulin therapy. The sample consisted of 60 Type II DM patients and consisted of 30 intervention groups and 30 control groups. Results: There were significant results on the level of knowledge (p=0.043), accuracy of insulin use (p=0.002), and insulin injection skills (p=0.017) in patients in the intervention group before and after education, but there was no significant difference in the control group. In addition, in the intervention group, there was a substantial and controlled decrease in GDP and HbA1c levels with a value of (p=0.000), while in the control group, there were no significant results with (p=0.104). Conclusion: Our findings highlight the role of insulin injection techniques (injection method, injection site, insulin pen use, and dosage) in controlling FPG and HbA1c glycemic levels in patients with Type II DM.